PENGEMBANGAN KAPASITAS INSTITUSI PERBANKAN SYARIAH DALAM PENYEDIAAN INFRASTRUKTUR JARINGAN, SDM DAN PRODUK - Agus Sumantri, Bambang (LIPI, 2014)
Writing in the journal aims to analyze the development ofinstitutional capacity, Islamic banking, network infrastructure,human resources and products of Islamic banking in Indonesiafrom 2003 to 2013. Where characteristics of a research libraryjournal writing.